Use of wind power generation blade of resin composition as gel coating / reading edge protective agent

A urethane resin composition with integrated urethane and carbonate structures addresses installation complexity and erosion resistance issues in wind power generation blades, ensuring efficient and durable leading edge protection.

JP2025007472APending Publication Date: 2025-01-17RESONAC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023108901
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing leading edge protection systems for wind power generation blades suffer from installation complexity, potential aerodynamic deterioration, and inadequate erosion resistance, leading to reduced power generation efficiency.

Method used

A resin composition containing a urethane resin with both urethane and carbonate structures is used as a gel coat and leading edge protectant, applied during blade manufacturing to provide excellent erosion resistance without compromising aerodynamic properties.

Benefits of technology

The solution reduces construction effort, maintains aerodynamic characteristics, and offers superior erosion resistance, enhancing the durability and efficiency of wind power generation blades.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007472000001_ABST
    Figure 2025007472000001_ABST
Patent Text Reader

Abstract

To provide use of various types of wind power generation blades of a resin composition which enables formation of a reading edge protective agent that has little labor for construction, can avoid lowering of aerodynamic characteristics and is excellent in erosion resistance, as a reading edge protective agent.SOLUTION: There is provided use of a wind power generation blade of a resin composition containing an urethane resin having an urethane structure and a carbonate structure in the same molecule as a gel coating / reading edge protective agent.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to the use of a resin composition as a gel coat and leading edge protectant for wind turbine blades. [Background technology]

[0002] Wind turbine blades are becoming larger in order to maximize power generation efficiency. As wind turbine blades become larger, damage or wear (erosion) of the leading edge of the wind turbine blade caused by rain or sand becomes an issue. Erosion reduces the aerodynamic characteristics of the wind turbine blade, resulting in reduced power generation efficiency. To prevent erosion, leading edge protection (LEP) is attached to the wind turbine blade. To date, different types of LEPs have been developed, including sheet type, paint type, and mold type.

[0003] US Patent Publication No. 2020 / 0040869 describes a method for applying a protective layer to an outer surface of a wind turbine rotor blade, the method including the steps of preparing a protective layer for application to the outer surface of the rotor blade, providing an air outlet channel between the rotor blade and the protective layer, attaching the protective layer to the outer surface of the rotor blade, and extracting air through the air outlet channel.

[0004] Patent document 2 (WO 2012 / 102294) describes a blade body which is made of fibre-reinforced plastic (FRP) and has a laminated protective sheet adhered to at least a part of the leading edge of the blade body, the laminated protective sheet having, in order from the blade body side, an adhesive layer, an intermediate fabric layer and a durable surface layer.

[0005] US Patent Publication No. 2021 / 0130647 describes a coating material composition used for the manufacture of erosion-stable coatings used as erosion protection, especially edge protection for rotor blades. The composition comprises a stock component and a hardener component, the stock component comprising at least one trifunctional polycaprolactone polyol, at least one polycarbonate diol or at least one trifunctional polycaprolactone polyol and polycarbonate diol, and the hardener component comprises at least one crystallization-resistant isocyanate-functional prepolymer.

[0006] Patent document 4 (WO 2016 / 075619) describes a method for making a protective cover for a wind turbine blade, characterized in that a) mixing a polyol and a butanediol, b) conditioning and degassing the mixture according to a), c) conditioning and degassing an isocyanate, d) pumping the degassed mixture according to b) and the degassed isocyanate according to c) through a mixhead into a mould, e) curing in the mould, and f) removing the cured article from the mould.

[0007] Non-patent document 1 (Wind Energy Utilization Symposium, 2021, Vol. 43, p. 210) states that when an erosion protection sheet is applied to a wind turbine blade, the aerodynamic characteristics of the wind turbine blade are reduced due to a step that occurs at the boundary between the wind turbine blade and the protective sheet. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] US Patent Application Publication No. 2020 / 0040869 [Patent Document 2] International Publication No. 2012 / 102294 [Patent Document 3] US Patent Application Publication No. 2021 / 0130647 [Patent Document 4] International Publication No. 2016 / 075619 [Non-patent literature]

[0009] [Non-Patent Document 1] Hirokazu Kawabata, "Aerodynamic Performance Evaluation of Blades with Erosion Protection Sheets," Wind Energy Utilization Symposium, 2021, Vol. 43, p. 210 Summary of the Invention [Problem to be solved by the invention]

[0010] The protective layer described in Patent Document 1 is a sheet applied in a post-process after the blade is manufactured, and the application is time-consuming. In addition, if the protective layer is applied in a post-process, as described in Non-Patent Document 1, the aerodynamic characteristics of the blade may be reduced due to a step that occurs at the boundary between the protective layer and the blade. The laminated protective sheet described in Patent Document 2 is attached to the blade by an adhesive layer, so that the laminated protective sheet may peel off from the blade after long-term use, resulting in reduced aerodynamic characteristics or generating noise. If the thickness of the protective layer or laminated protective sheet is set to, for example, 300 μm or more in order to ensure erosion resistance for a long period of time, the aerodynamic characteristics of the blade will be significantly reduced.

[0011] The coating material composition described in Patent Document 3 has excellent workability, but since it has low curability, it is difficult to obtain a sufficient level of erosion resistance.

[0012] The method described in Patent Document 4 requires that the protective cover be molded in advance to match the shape of the blade, which limits the blades that can be used. The thickness of the molded protective cover also tends to be large, which can easily lead to a decrease in the aerodynamic characteristics of the blade.

[0013] Also, when applying the sheet, coating or molding to the blade, it may be necessary to strip or remove any coating, such as a gel coat, on the blade surface to improve adhesion.

[0014] The present disclosure provides the use of a resin composition capable of forming an LEP that requires little application effort, avoids a decrease in aerodynamic characteristics, and has excellent erosion resistance, as a leading edge protective agent for various types of wind power generation blades. [Means for solving the problem]

[0015] The inventors have discovered that by using a resin composition containing a urethane resin having a urethane structure and a carbonate structure in the same molecule as a gel coat and leading edge protective agent during the manufacture of wind power blades, it is possible to reduce the effort required for application, avoid a decrease in aerodynamic characteristics, and impart an LEP with excellent erosion resistance to various types of wind power blades, and have completed the present invention.

[0016] The present disclosure includes the following aspects.

[0017] [Aspect 1] Use of a resin composition containing a urethane resin having a urethane structure and a carbonate structure in the same molecule as a gel coat and leading edge protective agent for wind power generation blades. [Aspect 2] 2. The use according to embodiment 1, wherein the urethane resin is a urethane (meth)acrylate resin. [Aspect 3] 3. The use according to any one of the preceding claims, wherein the resin composition further comprises an epoxy (meth)acrylate resin. [Aspect 4] The use according to any one of aspects 1 to 3, wherein the resin composition comprises 10% by mass to 90% by mass of the urethane resin. [Aspect 5] The use according to any one of aspects 1 to 4, wherein the urethane resin is a reaction product of a composition containing a polycarbonate polyol and a polyisocyanate, and a molar ratio (OH [mol] / NCO [mol]) of a hydroxyl group of the polycarbonate polyol to an isocyanato group of the polyisocyanate is 0.5 to 0.9. [Aspect 6] The use according to aspect 5, wherein the polycarbonate polyol has a number average molecular weight of 500 to 10,000. [Aspect 7] 7. The use of any one of claims 5 to 6, wherein the polyisocyanate comprises a cycloaliphatic polyisocyanate. [Aspect 8] The use according to any one of aspects 1 to 7, wherein the urethane resin has a number average molecular weight of 500 to 30,000. [Aspect 9] The use according to any one of the preceding aspects, wherein the wind power blade has a blade length of 10 m or more. Effect of the Invention

[0018] According to the present disclosure, LEPs that require little construction effort, can avoid a decline in aerodynamic characteristics, and have excellent erosion resistance can be formed on various types of wind power generation blades. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a schematic cross-sectional view of a wind power generating blade according to one embodiment. [Diagram 2] FIG. 2 is an explanatory diagram of a method for manufacturing a wind power generation blade according to an embodiment using a vacuum-assisted impregnation method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings. The present disclosure is not limited to the following embodiments, and can be modified in various ways within the scope of the present invention.

[0021] In the present disclosure, when a range of numerical values ​​is given, the numerical values ​​at both ends are the upper and lower limits, respectively, and are included in the range.

[0022] In this disclosure, "(meth)acrylic" means acrylic or methacrylic, "(meth)acrylate" means acrylate or methacrylate, and "(meth)acryloyloxy" means acryloyloxy or methacryloyloxy.

[0023] In this specification, an "ethylenically unsaturated bond" means a double bond formed between carbon atoms other than carbon atoms forming an aromatic ring, and an "ethylenically unsaturated monomer" means a monomer having an ethylenically unsaturated bond.

[0024] In the present disclosure, the "weight average molecular weight" and the "number average molecular weight" are values ​​measured at room temperature (23°C) using gel permeation chromatography (GPC) under the following conditions and obtained using a standard polystyrene calibration curve. Equipment: Shodex (trademark) GPC-101 (Resonac Co., Ltd.) Column: Shodex (trademark) LF-804 (Resonac Co., Ltd.) Column temperature: 40℃ Sample: 0.2% by mass solution of sample in tetrahydrofuran Flow rate: 1mL / min Eluent: Tetrahydrofuran Detector: Shodex (trademark) RI-71S (Resonac Corporation)

[0025] [Used as a gel coat and leading edge protector for wind turbine blades] In one embodiment, there is provided a use of a resin composition containing a urethane resin having a urethane structure and a carbonate structure in the same molecule as a gel coat and leading edge protective agent for wind power generation blades.

[0026] By using the resin composition, the formation and arrangement of a coating that can be used as a leading edge protection material can be performed during the manufacture of the wind power blade, shortening the process and allowing the coating to be applied to wind power blades of various shapes. In addition, since the coating can be heat cured in the heating step for hardening the matrix resin, a coating having high mechanical strength and bonding strength can be applied to the wind power blade. Furthermore, since the coating is formed along the shape of the mold surface, it does not affect the aerodynamic characteristics of the wind power blade, and a decrease in power generation efficiency can be prevented.

[0027] Fig. 1 is a schematic cross-sectional view of a wind power generating blade according to one embodiment. In Fig. 1, the wind power generating blade 10 is shown as a part, and includes a fiber-containing substrate 14 and a coating 12 partially disposed on the leading edge side of the fiber-containing substrate 14. The surfaces of the coating 12 and the fiber-containing substrate 14 are continuous along the mold surface used in manufacturing the wind power generating blade 10, and there is no step at the boundary between the coating 12 and the fiber-containing substrate 14.

[0028] [Resin composition] The resin composition of one embodiment includes a urethane resin having a urethane structure and a carbonate structure in the same molecule. The urethane resin having a urethane structure and a carbonate structure in the same molecule has both high mechanical strength and excellent elongation properties. Therefore, as a leading edge protection material, a coating having excellent erosion resistance can be formed.

[0029] <Urethane resin> The urethane resin having a urethane structure and a carbonate structure in the same molecule can be obtained by polyaddition reaction of at least a polyisocyanate and a polyol, and at least one of the polyisocyanate and the polyol has a carbonate structure. The urethane resin may be used alone or in combination of two or more kinds.

[0030] Examples of polyisocyanates include aromatic polyisocyanates such as 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, polymethylene polyphenyl diisocyanate, xylylene diisocyanate, phenylene diisocyanate, and triphenylmethane triisocyanate; alicyclic polyisocyanates such as 4,4'-methylenebiscyclohexyl diisocyanate, isophorone diisocyanate, and cyclohexane-1,3-diylbis(methylene) diisocyanate; and aliphatic polyisocyanates such as hexamethylene diisocyanate and trimethylhexamethylene diisocyanate; as well as adducts, isocyanurates, and biurets of these polyisocyanates. The polyisocyanate may be used alone or in combination of two or more kinds.

[0031] From the viewpoint of the mechanical strength and weather resistance of the coating, the polyisocyanate preferably contains an alicyclic polyisocyanate, and more preferably contains at least one selected from the group consisting of 4,4'-methylenebiscyclohexyl diisocyanate and isophorone diisocyanate.

[0032] As the polyol, polycarbonate polyol capable of introducing a carbonate structure into the urethane resin is generally used. The polycarbonate polyol can be synthesized from an alkanediol and a carbonic acid diester as raw materials under an ester exchange catalyst. Examples of the alkanediol include 1,6-hexanediol, 1,5-pentanediol, 1,4-butanediol, and 2-methyl-1,3-propanediol. The polycarbonate polyol can form a coating having excellent mechanical strength and elongation properties. The polyol may be used alone or in combination of two or more kinds.

[0033] The number average molecular weight (Mn) of the polycarbonate polyol is preferably 500 or more, more preferably 600 or more, and even more preferably 700 or more, and is preferably 10,000 or less, more preferably 8,000 or less, and even more preferably 5,000 or less, from the viewpoint of the mechanical strength and elongation properties of the coating. Any combination of these lower limit values ​​and upper limit values ​​may be used. The number average molecular weight of the polycarbonate polyol is preferably 500 to 10,000, more preferably 600 to 8,000, and even more preferably 700 to 5,000. If Mn is 500 or more, a coating having excellent mechanical strength can be formed. If Mn is 10,000 or less, a coating having excellent elongation properties can be formed.

[0034] The polyol may contain a low molecular weight polyol as a chain extender. The low molecular weight polyol increases the molecular weight of the urethane resin, and can further increase the mechanical strength of the coating. Examples of low molecular weight polyols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,10-decanediol, 1,1-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecanedimethanol, xylylene glycol, bis(p-hydroxy)diphenyl, bis(p-hydroxyphenyl)propane, 2,2-bis[4-(2-hydroxyethoxy)phenyl]propane, bis[4-(2-hydroxyethoxy)phenyl]sulfone, and 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane. The low molecular weight polyols may be used alone or in combination of two or more.

[0035] The amount of polyisocyanate used can be designed based on the molar ratio (OH [mol] / NCO [mol]) of the hydroxyl group of the polyol to the isocyanato group of the polyisocyanate. The molar ratio is preferably 0.5 or more. The molar ratio is preferably 0.9 or less, more preferably 0.8 or less, and even more preferably 0.7 or less. Any combination of these lower limit values ​​and upper limit values ​​may be used. The molar ratio is preferably 0.5 to 0.9, more preferably 0.5 to 0.8, and even more preferably 0.5 to 0.7. When the molar ratio is 0.9 or less, the mechanical strength of the coating can be increased. When the molar ratio is 0.5 or more, the elongation property of the coating can be increased.

[0036] In an embodiment in which the urethane resin is a reaction product of a composition containing a polycarbonate polyol and a polyisocyanate, the molar ratio (OH [mol] / NCO [mol]) of the hydroxyl group of the polycarbonate polyol to the isocyanato group of the polyisocyanate is preferably 0.5 or more. The molar ratio is preferably 0.9 or less, more preferably 0.8 or less, and even more preferably 0.7 or less. Any combination of these lower limit values ​​and upper limit values ​​may be used. The molar ratio is preferably 0.5 to 0.9, more preferably 0.5 to 0.8, and even more preferably 0.5 to 0.7.

[0037] The reaction temperature of the polyaddition reaction is not particularly limited, but is preferably from 20°C to 200°C, more preferably from 50°C to 150°C, and even more preferably from 80°C to 120°C.

[0038] The polyaddition reaction may be carried out using a catalyst. Examples of the catalyst include amine compounds such as triethylamine, N-ethylmorpholine, triethylenediamine, and diazabicycloundecene; organotin compounds such as trimethyltin laurate and dibutyltin dilaurate; organotitanium compounds; and organolead compounds such as lead octylate. The catalyst may be used alone or in combination of two or more.

[0039] The polyaddition reaction may be carried out substantially in the absence of a solvent, or in the presence of a solvent. Examples of the solvent include dimethylformamide, diethylformamide, dimethylacetamide, dimethylsulfoxide, tetrahydrofuran, methylisobutylketone, dioxane, cyclohexanone, benzene, toluene, and ethylcellosolve. The solvent may be used alone or in combination of two or more.

[0040] The urethane resin is preferably a urethane (meth)acrylate resin. The urethane (meth)acrylate resin can form a coating with high mechanical strength by being heat cured. As the urethane (meth)acrylate resin, for example, a resin obtained by introducing a (meth)acryloyl group into the terminal hydroxyl group or isocyanato group of the urethane resin obtained by reacting the polyisocyanate with the polyalcohol can be used. The urethane (meth)acrylate resin may be used alone or in combination of two or more kinds.

[0041] In the synthesis of urethane (meth)acrylate resin, when introducing a (meth)acryloyl group, for example, a method of reacting a terminal isocyanato group with a hydroxyl group-containing (meth)acrylic compound, or a method of reacting a terminal hydroxyl group with an isocyanato group-containing (meth)acrylic compound can be used. Each of the hydroxyl group-containing (meth)acrylic compound and the isocyanato group-containing (meth)acrylic compound may be used alone or in combination of two or more kinds.

[0042] Examples of hydroxyl group-containing (meth)acrylic compounds include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone-modified hydroxyalkyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, tris(hydroxyethyl)isocyanuric acid di(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerin mono(meth)acrylate, and hydroxyethylacrylamide, of which 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, caprolactone-modified hydroxyalkyl (meth)acrylate, and hydroxyethylacrylamide are preferred.

[0043] Examples of the isocyanato group-containing (meth)acrylic compound include 2-(meth)acryloyloxyethyl isocyanate, 2-(meth)acryloyloxypropyl isocyanate, and 1,1-bis(acryloyloxymethyl)ethyl isocyanate.

[0044] The unreacted hydroxyl group-containing (meth)acrylic compound or the unreacted isocyanato group-containing (meth)acrylic compound remaining after synthesis of the urethane (meth)acrylate resin can be used as an ethylenically unsaturated monomer, which will be described later.

[0045] The number average molecular weight (Mn) of the urethane resin is preferably 500 or more, more preferably 700 or more, and even more preferably 1,000 or more, and is preferably 30,000 or less, more preferably 25,000 or less, and even more preferably 20,000 or less. Any combination of these lower limit values ​​and upper limit values ​​may be used. The number average molecular weight of the urethane resin is preferably 500 to 30,000, more preferably 700 to 25,000, and even more preferably 1,000 to 20,000. If the number average molecular weight of the urethane resin is 500 to 30,000, the mechanical strength and erosion resistance of the coating film will be better.

[0046] The resin composition contains a urethane resin in an amount of preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more. The resin composition contains a urethane resin in an amount of preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less. Any combination of these lower limit values ​​and upper limit values ​​may be used. The resin composition contains a urethane resin in an amount of preferably 10% by mass to 90% by mass, more preferably 20% by mass to 80% by mass, and even more preferably 30% by mass to 70% by mass. When the content of the urethane resin is 10% by mass or more, the erosion resistance of the coating film is better. When the content of the urethane resin is 90% by mass or less, the coatability of the resin composition is good. In the present disclosure, the content of the urethane resin is calculated as a solid content.

[0047] <Epoxy (meth)acrylate resin> The resin composition of one embodiment further comprises an epoxy (meth)acrylate resin. The epoxy (meth)acrylate resin is generally a compound having an ethylenically unsaturated bond obtained by a ring-opening reaction between an epoxy group of an epoxy compound having two or more epoxy groups and a carboxy group of an unsaturated monobasic acid having an ethylenically unsaturated bond and a carboxy group. The epoxy (meth)acrylate resin may be used alone or in combination of two or more kinds.

[0048] The epoxy compound is not particularly limited as long as it has two or more epoxy groups. For example, the epoxy compound may be at least one selected from bisphenol type epoxy compounds, hydrogenated bisphenol type epoxy compounds, and novolac phenol type epoxy compounds. These epoxy compounds can further improve the mechanical strength and erosion resistance of the coating.

[0049] Examples of bisphenol type epoxy compounds include those obtained by reacting a bisphenol compound such as bisphenol A, bisphenol F, bisphenol S, and tetrabromobisphenol A with epichlorohydrin or methylepichlorohydrin, and those obtained by reacting one or more glycidyl ethers of the above bisphenol compounds, one or more condensates of the above bisphenol compounds, and epichlorohydrin or methylepichlorohydrin.

[0050] Examples of hydrogenated bisphenol type epoxy compounds include those obtained by reacting hydrogenated bisphenol with epichlorohydrin or methylepichlorohydrin, and those obtained by reacting a glycidyl ether of hydrogenated bisphenol A with a bisphenol compound such as bisphenol A, bisphenol F, bisphenol S, and tetrabromobisphenol A.

[0051] Examples of novolak phenol type epoxy compounds include those obtained by reacting phenol novolak or cresol novolak with epichlorohydrin or methyl epichlorohydrin.

[0052] From the viewpoint of the mechanical strength of the coating, the epoxy compound is preferably at least one selected from the group consisting of bisphenol A type epoxy resins and hydrogenated bisphenol A type epoxy resins.

[0053] As the unsaturated monobasic acid, there is no particular limitation as long as it is a monocarboxylic acid having an ethylenic unsaturated bond.As the unsaturated monobasic acid, for example, (meth)acrylic acid, crotonic acid, and cinnamic acid can be mentioned.As the unsaturated monobasic acid, from the viewpoint of the mechanical strength and erosion resistance of the coating, (meth)acrylic acid is more preferable, and from the viewpoint of the mechanical strength of the coating, methacrylic acid is more preferable.

[0054] The amount of the unsaturated monobasic acid used is preferably 0.3 to 1.5 mol, more preferably 0.4 to 1.2 mol, and particularly preferably 0.5 to 1.0 mol, of the total amount of carboxyl groups in the unsaturated monobasic acid per mol of the total amount of epoxy groups in the epoxy compound. If the amount of the unsaturated monobasic acid used is within the above range, a coating film having high hardness can be obtained.

[0055] The epoxy (meth)acrylate resin can be synthesized by a known synthesis method, for example, a method in which an epoxy compound and an unsaturated monobasic acid are dissolved in a solvent as necessary in the presence of an esterification catalyst and reacted at 70 to 150°C, preferably 80 to 140°C, and more preferably 90 to 130°C.

[0056] Examples of the esterification catalyst include tertiary amines such as triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, 2,4,6-tris(dimethylaminomethyl)phenol, and diazabicyclooctane; phosphorus compounds such as triphenylphosphine and benzyltriphenylphosphonium chloride; and diethylamine hydrochloride. The esterification catalyst may be used alone or in combination of two or more.

[0057] The unreacted unsaturated monobasic acid remaining after synthesis of the epoxy (meth)acrylate resin can be used as an ethylenically unsaturated monomer, which will be described later.

[0058] The number average molecular weight (Mn) of the epoxy (meth)acrylate resin is not particularly limited, but is preferably 500 to 30,000, more preferably 700 to 25,000, and further preferably 1,000 to 20,000. If the number average molecular weight of the epoxy (meth)acrylate resin is 500 to 30,000, the mechanical strength and erosion resistance of the coating film will be better.

[0059] In one embodiment, the resin composition contains 1% by mass to 80% by mass, preferably 3% by mass to 70% by mass, and more preferably 5% by mass to 60% by mass of an epoxy (meth)acrylate resin. When the content of the epoxy (meth)acrylate resin is 1% by mass or more, the mechanical strength of the coating can be increased. When the content of the epoxy (meth)acrylate resin is 80% by mass or less, the elongation property of the coating can be increased. In the present disclosure, the content of the epoxy (meth)acrylate resin is calculated as a solid content.

[0060] <Dilutable Monomer> The resin composition may contain an ethylenically unsaturated monomer as a diluent monomer. The diluent monomer can adjust the viscosity of the resin composition to improve workability and coatability. The diluent monomer may be used alone or in combination of two or more.

[0061] Examples of the ethylenically unsaturated monomer include vinyl compounds such as styrene, vinyltoluene, t-butylstyrene, methoxystyrene, divinylbenzene, vinylnaphthalene, and acenaphthylene; diene compounds such as butadiene, 2,3-dimethylbutadiene, isoprene, and chloroprene; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and the like. (Meth)acrylate compounds such as acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, furfuryl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, allyl (meth)acrylate, isobornyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, tricyclodecanol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate; (meth)acrylamide, N,N-dimethyl (meth)acrylamide, unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosahexaenoic acid, sorbic acid, etc.; unsaturated dicarboxylic acids such as fumaric acid and maleic acid; unsaturated dicarboxylic acid diesters such as diethyl citraconic acid; monomaleimide compounds such as N-phenylmaleimide; N-(meth)acryloylphthalimide; cinnamic acid; and dihydroxycinnamic acid.

[0062] From the viewpoints of curing speed and mechanical strength of the coating, the ethylenically unsaturated monomer is preferably at least one selected from the group consisting of styrene, vinyl toluene, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, t-butyl (meth)acrylate, phenyl (meth)acrylate, isobornyl (meth)acrylate, and benzyl (meth)acrylate, and more preferably at least one selected from the group consisting of styrene, vinyl toluene, t-butyl methacrylate, and isobornyl acrylate.

[0063] The content of the ethylenically unsaturated monomer is preferably 10% by mass to 95% by mass, more preferably 30% by mass to 90% by mass, and even more preferably 50% by mass to 80% by mass, based on the total of the urethane resin, the epoxy (meth)acrylate resin, and the ethylenically unsaturated monomer. If the content of the ethylenically unsaturated monomer is within the above range, the mechanical strength of the coating can be further increased.

[0064] <Hardening agent> The resin composition may contain a radical polymerization initiator as a curing agent to promote curing. When the radical polymerization initiator is added to the resin composition, the curing of the resin composition starts. Therefore, for example, when the resin composition is stored, it is desirable to add the radical polymerization initiator to the resin composition just before the curing of the resin composition. When the resin composition is stored under conditions in which the radical polymerization reaction does not start, the curing agent can be contained in the resin composition in advance from the viewpoint of work efficiency. The curing agent may be used alone or in combination of two or more kinds.

[0065] The radical polymerization initiator is not particularly limited and can be appropriately selected depending on the application, curing conditions, etc. Examples of the radical polymerization initiator include a thermal radical initiator and a photoradical initiator, and a thermal radical initiator is preferred from the viewpoint of workability.

[0066] Examples of the thermal radical initiator include organic peroxides such as diacyl peroxides such as benzoyl peroxide; peroxy esters such as t-butyl peroxybenzoate; hydroperoxides such as cumene hydroperoxide; dialkyl peroxides such as dicumyl peroxide; ketone peroxides such as methyl ethyl ketone peroxide and acetyl acetone peroxide; peroxy ketals such as 1,1-dialkylperoxycyclohexane; alkyl peresters such as alkyl peroxydecanoate; and percarbonates such as peroxydicarbonate.

[0067] The amount of the radical polymerization initiator used is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, and even more preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the total of the urethane resin, the epoxy (meth)acrylate resin, and the ethylenically unsaturated monomer. If the content of the radical polymerization initiator is 0.1 parts by mass or more, the curing of the resin composition can be rapidly promoted. If the content of the radical polymerization initiator is 10 parts by mass or less, a good balance between productivity and cost is achieved.

[0068] <Curing accelerator> The resin composition may contain a curing accelerator in order to accelerate the radical polymerization reaction of the resin composition. The curing accelerator may be used alone or in combination of two or more kinds.

[0069] Examples of the curing accelerator include salts of metal elements and organic acids. Examples of the metal elements include cobalt, vanadium, and manganese. Specific examples of the curing accelerator include manganese octylate, cobalt octylate, zinc octylate, vanadium octylate, cobalt naphthenate, copper naphthenate, barium naphthenate, vanadium acetoacetate, cobalt acetoacetate, and iron acetoacetate. Examples of the curing accelerator include manganese octylate, cobalt octylate, and cobalt naphthenate.

[0070] The amount of the curing accelerator used is preferably 0.01 to 6.0 parts by mass, more preferably 0.02 to 4.0 parts by mass, and even more preferably 0.03 to 3.0 parts by mass, based on 100 parts by mass in total of the urethane resin, the epoxy (meth)acrylate resin, and the ethylenically unsaturated monomer. By setting the amount of the curing accelerator used within the above range, the radical polymerization reaction of the resin composition can be rapidly progressed at low temperature to room temperature, for example, in the temperature range of 5°C to 40°C.

[0071] <solvent> The resin composition may contain a solvent. The solvent may be derived from a solvent used in the synthesis of the urethane resin or the epoxy (meth)acrylate resin. Examples of the solvent include esters such as n-butyl acetate and n-propyl acetate; and aromatic hydrocarbons such as benzene, toluene, and xylene. In the present disclosure, the solvent does not include the diluting monomer. The content of the solvent can be appropriately determined depending on the application and the coating method. For example, the content of the solvent can be set so that the solid content of the resin composition is 10% by mass to 90% by mass, 20% by mass to 80% by mass, or 30% by mass to 70% by mass.

[0072] Additives The resin composition may further contain additives, such as dispersants, fillers, thixotropic agents, thixotropic aids, colorants, and polymerization inhibitors.

[0073] An example of the dispersant is DISPERBYK-2152 (manufactured by BYK Japan Ltd.).

[0074] Examples of the filler include calcium carbonate, aluminum hydroxide, fly ash, barium sulfate, talc, clay, glass flakes, glass powder, and wood flour. Hollow fillers such as glass microballoons, saran resin microballoons, acrylonitrile microballoons, and shirasu balloons can also be used as the filler.

[0075] Examples of the thixotropic agent include inorganic powders such as silica and clay. The thixotropic agent can adjust the rheological properties of the resin composition to improve the coatability. When the resin composition contains particles such as fillers and pigments, the thixotropic agent can suppress the settling of these particles to improve the storage stability of the resin composition.

[0076] Examples of thixotropy-imparting assistants include polyethylene glycol, glycerin, polyhydroxycarboxylic acid amide, organic quaternary ammonium salts, and BYK-R-605 (manufactured by BYK Japan Ltd.).

[0077] Examples of colorants include organic pigments, inorganic pigments such as titanium oxide, and dyes.

[0078] Examples of the polymerization inhibitor include hydroquinone, trimethylhydroquinone, p-benzoquinone, naphthoquinone, tert-butylhydroquinone, catechol, p-tert-butylcatechol, and 2,6-di-tert-butyl-4-methylphenol.

[0079] Other additives include, for example, antifoaming agents, ultraviolet absorbers, light stabilizers, thickeners, and plasticizers.

[0080] <viscosity> The viscosity of the resin composition is preferably 10 mPa·s to 20,000 mPa·s, more preferably 50 mPa·s to 15,000 mPa·s, and even more preferably 100 mPa·s to 10,000 mPa·s. By setting the viscosity of the resin composition within the above range, workability and coatability can be improved. In the present disclosure, the viscosity of the resin composition is defined as the shear viscosity at 25°C and a rotation speed of 100 rpm using a cone-plate viscometer in accordance with JIS K 5600-2-3:2014.

[0081] Hereinafter, each step of the manufacturing method of the wind power generation blade will be described with reference to FIG.

[0082] <Coating process> In the coating step, the resin composition is applied to at least a part of the surface of the mold to form a coating.

[0083] FIG. 2(a) shows a cross-sectional view of a mold 20. The mold 20 has a mold surface 22 and includes an internal heater 24 for heating the stack during a heating process. The mold 20 in FIG. 2 is shown forming a portion of a wind power blade. As shown in FIG. 2(b), a resin composition is applied to a portion of the mold surface 22 to form a coating 12. The coating 12 is formed on a portion of the mold surface 22 that corresponds to the leading edge of the wind power blade.

[0084] The resin composition can be applied to the surface of a mold using a known application means such as a spray, a brush, a roll, a trowel, a spatula, or a syringe.

[0085] The coating formed by application may be pre-cured, for example, at 5° C. to 40° C. for 10 minutes to 72 hours.

[0086] The thickness of the coating may vary depending on the shape of the wind power blade, the required mechanical strength, etc. In one embodiment, the thickness of the coating on the wind power blade is 0.5 mm or more. In one embodiment, the thickness of the coating is 2 mm or less. Any combination of these lower limit values ​​and upper limit values ​​may be used. In one embodiment, the thickness of the coating is 0.5 mm to 2 mm. By setting the thickness of the coating to 0.5 mm or more and 2 mm or less, a coating with high mechanical strength can be imparted to the wind power blade.

[0087] In one embodiment, the coating is partially formed on the mold surface. The coating is a leading edge protection material for a wind power blade. In this embodiment, the leading edge protection material can be a gel coat. That is, the coating functions as both a leading edge protection material and a gel coat.

[0088] A separate coating may be formed on the mold surface other than where the coating is formed, in one embodiment the coating is a leading edge protectant and the separate coating is a gel coat used on typical wind turbine blades.

[0089] After the resin composition is partially applied to the mold surface to form a coating, a second resin composition different from the above resin composition may be applied to cover the coating and at least a part of the mold surface to form a second coating. An example of the second resin composition is a gel coat agent used for general wind power generation blades.

[0090] <Placement process> In the disposing step, a fiber-containing substrate impregnated with a matrix resin is disposed on the coating to form a stack. Examples of the fiber-containing substrate impregnated with a matrix resin include prepregs containing glass fibers or carbon fibers.

[0091] The disposing step may include impregnating the fibrous substrate with a matrix resin on the coating to form a fibrous substrate. Impregnation may be performed using, for example, a hand lay-up method or a vacuum-assisted impregnation method.

[0092] Examples of the fiber substrate include substrates containing fibers such as glass fibers, carbon fibers, polyester fibers, aramid fibers, vinylon fibers, and cellulose nanofibers. Examples of the fiber substrate that can be used include short fibers, long fibers, twisted yarns, chops, chopped strand mats, continuous strand mats, rovings, nonwoven fabrics, roving cloths, woven fabrics, braids, three-dimensional woven fabrics, and three-dimensional braids. Examples of the nonwoven fabric include spunbond nonwoven fabrics and meltblown nonwoven fabrics. Examples of the woven fabric include plain weave, satin weave, and twill weave.

[0093] The matrix resin may be any resin commonly used in FRP molding, such as a thermosetting epoxy resin.

[0094] With reference to (c) and (d) of FIG. 2, a method for forming a fiber-containing substrate by impregnating a fiber substrate with a matrix resin on a coating using a vacuum-assisted impregnation method will be described. As shown in (c) of FIG. 2, a fiber substrate 142 is arranged so as to cover the coating 12 and the mold surface 24. As shown in (d) of FIG. 2, a sheet 26 is arranged on the fiber substrate 142 to make the space between the sheet 26 and the mold surface 22 airtight. An exhaust port 28 is provided at one end of the sheet 26. The exhaust port 26 is connected to a vacuum pump, and the space between the sheet 26 and the mold surface 22 can be placed under reduced pressure by operating the vacuum pump. A matrix resin supplying device 30 that contains a matrix resin 144 therein is installed at the other end of the sheet. The valve 32 is opened and the vacuum pump is operated to reduce the pressure in the space between the sheet 26 and the mold surface 22, whereby the fiber substrate 142 is impregnated with the matrix resin 144, and the fiber-containing substrate 14 is formed on the coating 12. The fiber-containing substrate 14 is mated with the coating 12 to form a stack 16 .

[0095] <Heating process> In the heating step, the stack is heated to form a molded product in which the coating and the fiber-containing substrate are bonded. The coating preferably includes a cured product of the resin composition, i.e., is a cured coating. The cured coating is more firmly bonded to the fiber-containing substrate, so that a molded product having superior erosion resistance can be obtained.

[0096] As shown in (e) of Fig. 2, the heater 24 is operated to heat the stack 16. As a result, the coating 12 and the fiber-containing substrate 14 are bonded together to form the wind power generation blade 10 shown in Fig. 1.

[0097] The heating temperature can be, for example, from 50° C. to 200° C. The heating time can be, for example, from 30 minutes to 24 hours.

[0098] When the fiber-containing substrate is a prepreg, for example, autoclave molding or press molding can be used.

[0099] In one embodiment, the coating is disposed at least on the tip of the leading edge of the wind power blade. The tip of the leading edge refers to a portion of the leading edge that extends from the end of the wind power blade farthest from the rotation axis by 1% to 50%, 5% to 40%, or 10% to 30% of the blade length of the wind power blade, for example. This embodiment is suitable for large wind power blades, in which erosion is likely to occur because the tip moves at high speed. The coating can be disposed on the entire leading edge including the tip, or on the entire surface of the wind power blade.

[0100] The blade length of the wind power generation blade is preferably 10 m or more, more preferably 20 m or more, and even more preferably 30 m or more. The blade length of the wind power generation blade may be, for example, 140 m or less, 100 m or less, or 80 m or less. Any combination of these lower limit values ​​and upper limit values ​​may be used. In one embodiment, the blade length of the wind power generation blade is 10 m to 140 m, 20 m to 100 m, or 30 m to 80 m.

[0101] By using the resin composition of the present disclosure, a leading edge protective material having excellent properties can be formed on a wind power generation blade. EXAMPLES

[0102] Examples, comparative examples and reference examples related to the present invention are shown below, but the present invention is not limited to these.

[0103] [Viscosity at 25℃] The viscosity of the resin composition was evaluated by the following procedure. In accordance with JIS K 5600-2-3:2014 "General test methods for paints - Part 2: Properties and stability of paints - Section 3: Viscosity (cone-plate viscometer method)", the shear viscosity was measured at 25°C and a rotation speed of 100 rpm using a cone-plate viscometer (RE-215U, manufactured by Toki Sangyo Co., Ltd., rotor: 1°34' x R24).

[0104] The physical properties of the molded products were evaluated according to the following procedures.

[0105] [Erosion resistance] Using a high-pressure washer (SH-0807, manufactured by Super Kogyo Co., Ltd.), a water pressure of 6.0 MPa, a water flow rate of 6 L / min, and a test piece-to-nozzle distance of 7 cm were used to directly hit a test piece measuring 50 mm x 60 mm x 2 mm (thickness) with a continuous water flow at 23°C for 30 minutes, after which the test piece was visually inspected for damage. The time required for damage to occur was taken as the erosion resistance.

[0106] [Adhesive strength] In accordance with JIS K 5600-5-7:2014 "General test methods for paints - Part 5: Mechanical properties of coatings - Section 7: Adhesion (pull-off method)", a coating was formed with a thickness of 0.5 mm on a standard glass epoxy plate (60 mm x 150 mm x 2 mm (thickness), manufactured by Nippon Test Panel Co., Ltd.), and a dolly (diameter 20 mm, made of aluminum) was fixed to the coating using an adhesive (Metallock (trademark), manufactured by Cemedine Co., Ltd.), and the adhesive strength was measured using an adhesion tester (Positest AT-A, manufactured by COTEC Co., Ltd.). The adhesive strength was defined as the average value measured with N=3.

[0107] [Resistance to humidity and heat cycles] A test piece (50 mm × 80 mm × 2 mm (thickness)) was placed in a thermo-hygrostat (PL-2J, manufactured by Espec Corporation) and subjected to 100 cycles of repeated heat and humidity cycles at -40°C for 6 hours and at 60°C and 98% relative humidity for 6 hours. The appearance was then visually inspected for the presence or absence of chalking, blisters, and cracks. A: No chalking, blisters or cracks B: No cracks, no chalking or blisters C: There were no cracks. D: Cracks occurred

[0108] The materials used in the synthesis of the urethane (meth)acrylate resin and the epoxy (meth)acrylate resin are shown in Table 1.

[0109] [Table 1]

[0110] The materials used in the preparation of the resin composition are shown below. Dry silica Leoloseal PM-20L (Tokuyama Corporation) Titanium oxide PFC-105 (manufactured by Ishihara Sangyo Kaisha, Ltd.) Glass powder CF0033 (Takara Standard Co., Ltd.) Glass flake (trademark) RCF-160N (manufactured by Nippon Sheet Glass Co., Ltd.) DISPERBYK-2152 (BYK Japan Co., Ltd.) 8% Cobalt Octylate (8% Cobalt Hexoate, manufactured by Toei Kako Co., Ltd.) Hardener 328E (t-butyl peroxybenzoate, cumene hydroperoxide mixture, manufactured by Nouryon Chemical Co., Ltd.) Percumyl (trademark) H-80 (cumene hydroperoxide, manufactured by NOF Corporation)

[0111] The urethane (meth)acrylate resin and the epoxy (meth)acrylate resin were synthesized by the following procedure.

[0112] [Synthesis Example 1: Urethane (meth)acrylate resin UAc-1] In a flask equipped with a stirrer, a reflux condenser, a thermometer, and a gas inlet tube, 142 g of 4,4'-methylenebiscyclohexyldiisocyanate (Desmodur W, manufactured by Sumika Covestro Urethane Co., Ltd.), 411 g of polycarbonate diol (ETERNACOLL PH-100, manufactured by UBE Corporation), and 0.4 g of dibutyltin dilaurate were charged and reacted for 4 hours at 80°C while heating and stirring. Then, 46 g of 2-hydroxyethyl methacrylate was charged, and the mixture was reacted for 4 hours at 80°C while blowing in dry air and heating and stirring, to obtain urethane (meth)acrylate resin UAc-1.

[0113] [Synthesis Examples 2 to 7: Urethane (meth)acrylate resins UAc-2 to UAc-7] Urethane (meth)acrylate resins UAc-2 to UAc-7 were obtained in the same manner as in Synthesis Example 1, except that the raw materials and their amounts were as shown in Table 2.

[0114] [Synthesis Example 8: Epoxy (meth)acrylate resin EAc-1] A flask equipped with a stirrer, a reflux condenser, a thermometer, and a gas inlet tube was charged with 683 g of bisphenol A type epoxy resin (Epomic R140, manufactured by Mitsui Fine Chemicals, Inc.), 313 g of methacrylic acid, 3.0 g of triethylamine, and 0.6 g of hydroquinone, and reacted at 120°C while blowing in air. When the acid value became 5 mgKOH / g or less, the mixture was cooled to obtain an epoxy (meth)acrylate resin EAc-1.

[0115] [Synthesis Example 9: Epoxy (meth)acrylate resin EAc-2] An epoxy (meth)acrylate resin EAc-2 was obtained in the same manner as in Synthesis Example 8, except that the raw materials and their amounts were as shown in Table 2.

[0116] [Table 2]

[0117] The resin composition was prepared according to the following procedure.

[0118] [Example 1] The urethane (meth)acrylate resin UAc-1 obtained in Synthesis Example 1 above (40 g), vinyl toluene (60 g), 8% cobalt octylate (0.5 g), and curing agent 328E (1.5 g) were added and stirred at 2000 rpm for 1 minute using a planetary centrifugal mixer to obtain a resin composition of Example 1.

[0119] The resin composition was poured into a silicone mold 2 mm deep and left for 3 hours at 23°C for pre-curing and 6 hours at 70°C for post-curing to obtain a molded product of the resin composition. Pre-curing corresponds to the process of applying the resin composition to the mold surface to form a coating, and post-curing corresponds to the process of heating the stack of the coating and the fiber-containing substrate. The evaluation results of the resin composition and the molded product are shown in Table 3.

[0120] [Examples 2 to 15, Comparative Examples 1 to 4] A resin composition was obtained in the same manner as in Example 1, except that the raw materials and their amounts were as shown in Table 3. A molded article was obtained from the obtained resin composition in the same manner as in Example 1. The evaluation results of the resin composition and the molded article are shown in Table 3.

[0121] [Reference example 1~Reference example 3] Using the resin composition of Example 1, a molded article was obtained without performing post-curing but only pre-curing under the conditions shown in Table 3. The evaluation results of the molded article are shown in Table 3.

[0122] [Example 16] A molded article was obtained in the same manner as in Example 1, except that the resin composition of Example 1 was poured into a silicone mold with a depth of 0.1 mm. The evaluation results of the molded article are shown in Table 3.

[0123] [Table 3-1]

[0124] [Table 3-2]

[0125] [Table 3-3] [Industrial Applicability]

[0126] The resin composition of the present disclosure is suitable for producing leading edge protection materials for wind power generation blades. [Explanation of symbols]

[0127] 10 Wind turbine blades 12 Coating 14 Fiber-containing substrates 142 Fiber base material 144 Matrix Resin 16 Stack 20 Mold 22 Mold surface 24 Heater 26 sheets 28 Exhaust port 30 Matrix resin supply device 32 Valve

Claims

1. Use of a resin composition containing a urethane resin having a urethane structure and a carbonate structure in the same molecule as a gel coat and leading edge protective agent for wind power generation blades.

2. The use according to claim 1 , wherein the urethane resin is a urethane (meth)acrylate resin.

3. The use according to claim 1 or 2, wherein the resin composition further comprises an epoxy (meth)acrylate resin.

4. The use according to claim 1 or 2, wherein the resin composition contains 10% by mass to 90% by mass of the urethane resin.

5. The use according to claim 1 or 2, wherein the urethane resin is a reaction product of a composition containing a polycarbonate polyol and a polyisocyanate, and the molar ratio (OH [mol] / NCO [mol]) of a hydroxyl group of the polycarbonate polyol to an isocyanato group of the polyisocyanate is 0.5 to 0.

9.

6. The use according to claim 5, wherein the polycarbonate polyol has a number average molecular weight of 500 to 10,000.

7. The use of claim 5 , wherein the polyisocyanate comprises a cycloaliphatic polyisocyanate.

8. The use according to claim 1 or 2, wherein the number average molecular weight of the urethane resin is from 500 to 30,000.

9. 3. The use according to claim 1 or 2, wherein the wind power blade has a blade length of 10 m or more.

Citation Information

Patent Citations

  • Method of applying a protective layer to a wind turbine rotor blade

    US20200040869A1

  • Coating material composition, coatings produced therefrom and the use thereof as erosion protection

    US20210130647A1

  • Blade and protective laminated sheet for blade

    WO2012102294A1

  • Polyurethane material, process for preparing such material and protective cover for wind turbine blade

    WO2016075619A1